1979
DOI: 10.1038/bjc.1979.54
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal cancer studies in the Caspian Littoral of Iran: Results of a case-control study

Abstract: Summary.-The results are presented of a case-control study conducted in the north of Iran. The main aim was to study factors identified in a previous study as potentially causally related to cancer of the oesophagus. Other tumours (lung, stomach, breast, large bowel, larynx and pharynx) were included to distinguish findings specific for oesophageal cancer from general characteristics of cancer patients, due for example to ascertainment bias, and to verify that expected associations, such as between lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
116
3
3

Year Published

1981
1981
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(128 citation statements)
references
References 10 publications
5
116
3
3
Order By: Relevance
“…These two exposures are major risk factors for oesophageal squamous cell carcinoma in Western populations (Brown et al, 1994(Brown et al, , 2001), but play a much smaller role in such high-risk areas, such as Linxian (Tran et al, 2005) or northeastern Iran (Cook-Mozaffari et al, 1979;Islami et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These two exposures are major risk factors for oesophageal squamous cell carcinoma in Western populations (Brown et al, 1994(Brown et al, , 2001), but play a much smaller role in such high-risk areas, such as Linxian (Tran et al, 2005) or northeastern Iran (Cook-Mozaffari et al, 1979;Islami et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Etiologic factors responsible for these high rates are largely unknown (Islami et al, 2004), and only two studies have examined the role of diet in association with oesophageal cancer in this area (Hormozdiari et al, 1975;Cook-Mozaffari et al, 1979). Residents in the high incidence areas had lower intake of vitamins A and C, riboflavin, animal proteins and fresh vegetables and fruits and a higher consumption of sheep and goat milk than that of residents in other areas (Hormozdiari et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional deficiencies have been suspected as risk factors for squamous cell oesophageal cancer for more than 20 years in Eastern countries, like Iran and China (Cook-Mozaffari et al, 1979;Thurnham et al, 1988;Hu et al, 1994). Recent reviews reported on the protective role of vegetables and fruits (Cheng and Day 1996;World Cancer Research Fund 1997).…”
mentioning
confidence: 99%